2004
DOI: 10.1080/00207450490269499
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit/Hyperactivity Disorder and Working Memory in Clinically Referred Adults

Abstract: A current theory of attention deficit/hyperactivity disorder (ADHD) implicates a dysfunction in working memory as a significant factor in ADHD. The Working Memory Indexes of the Wechsler Adult Intelligence Scale--Third Edition (WAIS-III; The Psychological Corporation, 1997a) and the Wechsler Memory Scale--Third Edition (WMS-III; The Psychological Corp -oration, 1997b) were used to evaluate this theory. Seventy adults clinically diagnosed with ADHD (mean age = 25) and who were previously administered the WAIS-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…Difficulty level is determined by the amount of information that has to be held in memory in order to successfully complete the problem. This task does place demands on the WM system; however, other factors likely contribute to accuracy on this task, such as mathematical efficiency (Stearns, Dunham, McIntosh, & Dean, 2004). Math anxiety has also been linked to impaired performance on WM tasks that contain a mathematical element, such as computation span (Ashcraft & Kirk, 2001).…”
Section: Clinical Assessment Of Wmmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulty level is determined by the amount of information that has to be held in memory in order to successfully complete the problem. This task does place demands on the WM system; however, other factors likely contribute to accuracy on this task, such as mathematical efficiency (Stearns, Dunham, McIntosh, & Dean, 2004). Math anxiety has also been linked to impaired performance on WM tasks that contain a mathematical element, such as computation span (Ashcraft & Kirk, 2001).…”
Section: Clinical Assessment Of Wmmentioning
confidence: 99%
“…For example, Stearns et al (2004) investigated the relationship between WM and ADHD in adults using the WM Indices from the WAIS-III and the WMS-III. The results did not reveal significant correlations between WM and self-reported ADHD symptoms despite the fact that WM impairment is commonly observed in the disorder.…”
Section: Clinical Assessment Of Wmmentioning
confidence: 99%
“…On the other hand, existing studies have found arithmetic subtest requires diverse cognitive processes such as attention/concentration, verbal comprehension, and mathematical skills as well as WM. 25,27) It also has the lowest factor loading among clinical WM constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Although it might seem like the Canadian norms might be most appropriate and beneficial for use in Canada, the lack of research using these norms tend to make clinicians wary about adopting them. To date, there is a growing body of research that provides data relating to WAIS-III performance in clinical and healthy populations using the American norms (e.g., Axelrod, Dingell, Ryan, & Ward, 2000;Blyer, Gold, Iannone, & Buchanan, 2000;Bowler, Gysens, & Hartney, 2003;Dickinson & Coursey, 2002;Donders, Tulsky, & Zhu, 2001a;Langeluddecke & Lucas, 2003;Martin et al, 2002;Ryan, Arb, Paul, & Kreiner, 2000;Ryan, Lopez, & Werth, 1999;Stearns, Dunham, McIntosh, & Dean, 2004;The Psychological Corporation, 1997;Townsend, Malla, & Norman, 2001). However, few studies are available that present data using the Canadian normative system.…”
Section: Introductionmentioning
confidence: 96%